Zeolites and related microporous materials : state of the art 1994 : proceedings of the 10th International Zeolite Conference, Garmisch-Partenkirchen, Germany, July 17-22, 1994. - Weitkamp, J. (Jens) (Studies in surface science and catalysis, 1994)
These proceedings, comprising 7 plenary lectures, 100 oral and 175 poster presentations, reflect present activities in the field of microporous materials. The International Zeolite Conferences are devoted to all aspects of zeolite science and technology. The term "zeolite" is to be understood in its broadest sense comprising all kinds of crystalline microporous materials regardless of their composition (e.g. aluminosilicates and other metallosilicates, silica, aluminophosphates, gallophosphates etc.), occurring in nature or synthesized by man. Mesoporous silica, aluminosilicates and other metallosilicates, as recently discovered are also included. Zeolite catalysis continues to be an area of particular interest, not only the classical hydrocarbon conversions but also zeolite catalysis of oxidation reactions, formation of a greater variety of organic compounds and environmental catalysis. Much work has been done on the synthesis of zeolites and zeolite-like materials, which is reflected in the large number of contributions to these proceedings. Improvement of techniques for investigation has stimulated interest in adsorption and diffusion studies. Other areas enjoying increasing attention are modelling, theory, and novel materials